Integration of Renewable Energy Sources in future power systems: The role of storage. (March 2015) - Weitemeyer, Stefan; Kleinhans, David; Vogt, Thomas; Agert, Carsten
Abstract: Integrating a high share of electricity from non-dispatchable Renewable Energy Sources in a power supply system is a challenging task. One option considered in many studies dealing with prospective power systems is the installation of storage devices to balance the fluctuations in power production. However, it is not yet clear how soon storage devices will be needed and how the integration process depends on different storage parameters. Using long-term solar and wind energy power production data series, we present a modelling approach to investigate the influence of storage size and efficiency on the pathway towards a 100% RES scenario. Applying our approach to data for Germany, we found that up to 50% of the overall electricity demand can be met by an optimum combination of wind and solar resources without both curtailment and storage devices if the remaining energy is provided by sufficiently flexible power plants. Our findings show further that the installation of small, but highly efficient storage devices is already highly beneficial for the RES integration, while seasonal storage devices are only needed when more than 80% of the electricity demand can be met by wind and solar energy. Our results imply that a compromise between the installation of additional generation capacities and storage capacities is required. Highlights: Necessity and effect of energy storages from a meteorological perspective. Influence of storage size and efficiency on their integration into energy systems. Installation of small, but highly efficient storage devices is highly beneficial. Seasonal storages are needed when more than 80% of the electricity demand is met by RES.